Comparison Performance Of Induction Motor Using SVPWM And Hysteresis Current Controller - Patakor, Fizatul Aini; Sulaiman , Marizan; Ibrahim, Zulkifilie (Little Lion Scientific Islamabad Pakistan, 2011)
-